PENDUGAAN CADANGAN KARBON TANAMAN HORTIKULTURA DI LAHAN BEKAS TAMBANG TIMAH DI KECAMATAN BELINYU, KABUPATEN BANGKA - Efita Karunia Harita; Anggraeni; Eddy Nurtjahya; Iwan Hilwan (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to measure carbon reserves in horticultural plants planted on former tin mining land and compared with horticultural plants on non-mining land in Belinyu District, Bangka Regency. The time and place of this study were carried out from February 2023 to July 2023 in Gunung Pelawan Village, Bukit Ketok Village, Bangka Regency. The research method used was the purposive sampling method. The analysis method used percentage analysis. The results of the study showed that the carbon reserve content of plants plantedon former tin mining land was lower as an adaptation to former tin mining land that experienced drought stress and high light intensity but was not significantly different from plants planted on non-tin mining land. This is thought to be because the care given to plants on former tin mining land was quite good. Future research can be carried out by combining morphological, anatomical and physiological observations, as well as analysis of carbon reserve content in horticultural plants as a response to the former tin mining land environment.